Inhibiting the NLRP3 Inflammasome With MCC950 Ameliorates Isoflurane-Induced Pyroptosis and Cognitive Impairment in Aged Mice - Fan, Yunxia; Du, Liwu; Fu, Qun; Zhou, Zhiqiang; Zhang, Jingyu; Li, Guomin; Wu, Jing (Frontiers in Cellular Neuroscience, 2018)
Nod-like receptor protein 3 (NLRP3) inflammasome activation has been implicated in the pathogenesis of general anesthesia (GA)-induced neuroinflammation and cognitive impairment in aged rodents. However, the cellular basis for cognitive impairment is still not fully understood, and effective pharmacologic agents targeting the NLRP3 inflammasome during GA are lacking. This study explores the protective effects of the NLRP3 inflammasome inhibitor MCC950 on pyroptosis and cognitive impairment in aged mice exposed to isoflurane. Seventy-two 15-month-old male C57BL/6 mice were randomized to receive 2 h of 1.5% isoflurane plus 30% oxygen or 30% oxygen alone, respectively. MCC950 (10 mg/kg) or vehicle was intraperitoneally administered 30 min before gas inhalation. Brain tissues were harvested for histochemical analysis and biochemical assays. Learning and memory abilities were evaluated by behavioral tests. We found that isoflurane GA caused upregulations of hippocampal NLRP3, cleaved caspase-1, interleukin-1β (IL-1β) and IL-18 and the activation of pyroptosis, which is NLRP3 inflammasome-dependent; this consequently gave rise to neuronal damage and cognitive impairment in aged mice. Interestingly, pretreatment with NLRP3 inflammasome inhibitor MCC950 not only provided a neuroprotective effect against the inflammasome activation but also ameliorated pyroptosis and cognitive impairment in aged mice exposed to isoflurane. Our data demonstrate that pyroptosis is involved in NLRP3 inflammasome-mediated isoflurane-induced cognitive impairment in aged mice and suggest that inhibiting the NLRP3 inflammasome with MCC950 may have clinically therapeutic benefits for elderly patients undertaking GA.